Acute Kidney Injury During Vancomycin Therapy in Critically Ill Children. Issue 6 (21st March 2013) - Totapally, Balagangadhar R.; Machado, Jacqueline; Lee, Helen; Paredes, Ana; Raszynski, Andre
<x xml:space="preserve">Abstract</x> Study Objective To determine the rate, risk factors, and outcome of vancomycin–associated acute kidney injury (AKI) in critically ill children. Design Retrospective cohort study. Setting Tertiary care children's hospital. Patients We reviewed the charts of children admitted to the pediatric intensive care unit during a 2‐year period who were treated with vancomycin. Courses of vancomycin interrupted by 3 days or more were counted separately. Patients were excluded if they received vancomycin treatment for fewer than 3 days, had preexisting renal failure, or had incomplete serum creatinine (Scr) data. Measurements and Main Results Demographic and laboratory data; vancomycin dose, duration, and concentrations; and concurrent use of nephrotoxic drugs were recorded. Acute kidney injury was defined as a decrease in estimated glomerular filtration rate of 50% or more from the beginning of vancomycin therapy. Descriptive statistics, step‐wise logistic regression, and repeated measures ANOVA were used to analyze the data. A total of 284 patients were included, for a total of 391 courses of vancomycin (272 children and 119 infants). The mean duration of vancomycin therapy was 6.9 ± 4.5 days. Forty nine (17.2%) patients developed AKI during 61 (15.6%) courses. Elevated Scr concentrations returned to baseline after stopping vancomycin in 53 (87%) courses. Mortality was higher in children who developed AKI (p<0.001; Fisher's exact test). Administration of nephrotoxic drugs (odds ratio 2.23, Confidence Interval 1.27–3.93) and presence of high blood urea nitrogen (BUN):Scr ratio before vancomycin therapy (p<0.05) were associated with AKI. The BUN and Scr concentrations significantly increased during vancomycin therapy and decreased after vancomycin was discontinued (p<0.05). Conclusions In critically ill children, the development of reversible AKI during vancomycin therapy is associated with administration of nephrotoxic drugs and an elevated BUN: Scr ratio.